The Effect of Work Motivation and Work Discipline on Employee Performance at the Residential and Land Housing Office of Cirebon Regency - Muhamad Alwi; Risqi Pratama (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to find out how work motivation and work discipline affect the performance of employees at the Cirebon Regency Housing, Settlement, and Land Office. The research was conducted using quantitative approaches and associative methods. A total of 75 employees were used as respondents to the saturated sample. After data collection, questionnaires were distributed using the Likert scale and then analyzed by multiple linear regression using the SPSS program version 25. The results of the study show that work motivation and work discipline have a positive and significant influence on employee performance, overall, work motivation and work discipline significantly improve the performance of employees in this office. Therefore, this research is expected to be the basis for government organizations to formulate human resource management policies, especially regarding how to increase motivation and work discipline so that they can achieve the best level of performance